Impact of various fermentation conditions on the Production of violacein by the novel isolate Chromobacterium vaccinii cv5 - VISHNU T.S; PALANISWAMY M (International Journal of Pharma and Bio Sciences, 2017)
The purple-coloured pigment violacein, produced mainly by bacteria of the genus Chromobacterium, had attracted and increased interest owing to its important biological activities and pharmacological potential. In the present study experiments were designed to investigate the effect of different fermentation conditions on the violacein production by novel isolate Chromobacterium vaccinii CV5. Different parameters were systematically manipulated in submerged fermentation to improve the yield of total violacein. The violacein production was maximum at Luria Bertani broth and also supported by the addition of glucose and tryptophan as carbon and nitrogen sources at 37°C with pH of 6.5 at 72 h incubation and agitation of 150 rpm.